Identification of a New Potential SARS-COV-2 RNA-Dependent RNA Polymerase Inhibitor via Combining Fragment-Based Drug Design, Docking, Molecular Dynamics, and MM-PBSA Calculations - El Hassab, Mahmoud A.; Shoun, Aly A.; Al-Rashood, Sara T.; Al-Warhi, Tarfah; Eldehna, Wagdy M. (Frontiers in Chemistry, 2020)
Recently, the world may never experience an outbreak like the coronavirus pandemic. Infections are increasing without reaching a peak. WHO has reported more than 14 million infections and nearly 600,000 confirmed deaths. Safety measures are insufficient and still no approved drugs for the COVID-19. Thus, it is necessary to develop a specific inhibitor for the COVID-19 infection. One of the most attractive targets in the virus life cycle is the polymerase enzyme responsible for the replication of virus genome. Here, we describe our Structure-Based Drug Design (SBDD) protocol for designing of a new potential inhibitor for COVID-19 polymerase. Firstly, the crystal structure of COVID-19 polymerase was retrieved from the protein data bank PDB ID (7bv2). Then, Fragment-Based Drug Design (FBDD) strategy was implemented using Discovery Studio 2016. The best five generated fragments were linked together using suitable carbon linkers to yield compound MAW-22. Thereafter, the strength of binding between compound MAW-22 and the COVID-19 polymerase was predicted by docking strategy using docking strategy. MAW-22 achieved high docking score, even more than the score achieved by Remdesivir indicating a very strong binding between MAW-22 and its target. Finally, three molecular dynamic simulation experiments were performed for 150 ns to validate our concept of design. The three experiments revealed that MAW-22 has a great potentiality to inhibit the COVID-19 polymerase than Remdesivir. Also, it thought that this study had proved SBDD to be the most suitable way that could open a new era in future drug development for COVID-19 infection.